THE IMPACT OF ELECTRICITY, CO₂ EMISSIONS, AND FOSSIL ENERGY ON INDONESIA'S ECONOMIC GROWTH - Nazla Salsabila; Jariah Abubakar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze Electrical Energy, CO2 Emissions and Fossil Energy on Economic Growth in Indonesia. This study uses secondary data from 1980-2023 obtained from the Central Statistics Agency. The data analysis method is the Autoregressive Distributed Lag. The results of the study show that in the short term, electrical energy shows a significant negative effect on economic growth. While CO2 emissions and fossil energy show a significant positive effect on economic growth. In the long term, electrical energy, CO2 emissions and fossil energy do not show a significant effect on economic growth.